(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The article discusses the increasing use of artificial intelligence (AI) in financial analysis, which is causing the sector to undergo a transformation. As a result, a modernised finance curriculum is required in order to provide aspiring analysts with the necessary abilities to operate in an AI-centric environment. This study investigates the fundamental elements that should be included in an updated curriculum and suggests possible classes that may be used to meet these requirements. The need of having a full understanding of artificial intelligence and data analysis, in addition to ethical and regulatory issues, is emphasised at this point. The experimental work achieves a harmonic balance between the traditional concepts of financial analysis and the applications of artificial intelligence, which is of the utmost relevance. The cornerstone of these new curriculums is comprised of theoretical and practical knowledge, which is augmented by case studies, hands-on projects, industry collaborations, research potential, and collaborative learning. Potential future financial analysts will be able to flourish in an environment driven by artificial intelligence (AI), respect ethical standards, make judgements that are well informed, and advance financial innovation ahead if these components are included into the curriculum for finance.